Short‐term effects of alternative cultivation practices on putting green infiltration rates. Issue 6 (5th September 2021) - Amgain, Naba R.; Fontanier, Charles H.; Martin, Dennis L.
Abstract: Core aerification iscommonly used to manage organic matter and improve soil physical conditions of putting greens. Most methods of core aerification are labor intensive and temporarily reduce the playability of greens. Less invasive cultivation techniques are available, but their specific effects on playability and drainage properties of greens are often less understood. The objective of this study was to assess the short‐term effects of air‐injection cultivation (AIC), sand‐injection cultivation (SIC), and hollow‐tine cultivation (HTC) on playability characteristics and soil physical properties of putting greens. A field study was conducted at the Oklahoma State University Turfgrass Research Center in Stillwater, OK, on a creeping bentgrass ( Agrostis stolonifera L. 'Penncross') green from September 2017 to September 2019. Cultivation type and timing of application were arranged in a split‐plot design with four replications. Cultivation type was defined as either AIC, SIC, or HTC, and each was applied in spring, summer, and fall. Compared with the control, HTC reduced surface firmness by 5% at 28 d after cultivation event (DACE), increased infiltration by 87% at 28 DACE, reduced ball roll distance by 6% up to 14 DACE, and reduced normalized difference vegetation index (NDVI) by 10% up to 14 DACE. Neither AIC nor SIC had a detectable effect on measured variables. Results suggest a single application of AIC or SIC has minimal short‐term effects on soil physical properties or surface playability of putting greens. Core Ideas: Alternative cultivation did not affect soil moisture, surface firmness, and infiltration rate. Hollow‐tine cultivation increased infiltration rate and reduced compaction of putting green. Air‐injection was effective at increasing infiltration rate directly at the injection hole of putting green.